"Looking sharp": Price typeface influences awareness of spending in mobile payment. Issue 6 (25th March 2022) - Park, Jaewoo; Velasco, Carlos; Spence, Charles
Abstract: We investigate whether the typeface used to display the purchase amount in the context of mobile payment influences consumers' awareness of spending. The evidence suggests that prices displayed in angular (vs. round) typeface increase the awareness of spending in the context of mobile payment via the perceived harshness of the typeface and the experienced pain of payment (Studies 1–3, 5, and 6). Angular (vs. round) typeface also has downstream consequences for payment behavior, indicating that the amount displayed with the angular typeface increases the hesitation to press the "pay" button (Studies 2 and 6). Our results also demonstrate that the typeface effect on the awareness of spending is moderated by the purchase amount (Study 3). The robust typeface effect documented for Japanese participants (Studies 1–3) is not observed in North Americans (Studies 4 and 5), highlighting the role of culture. Finally, we replicate the price typeface effect (Studies 1–3) in a situation that is closer to the context of real mobile shopping and demonstrate that price typeface impact people's willingness to spend on the next grocery shop (Study 6). Our research contributes to the scarce literature on addressing the profligacy issues associated with mobile payments and broadly cashless payments.